2021
DOI: 10.1371/journal.pone.0253131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of family "upward" intergenerational support on the health of rural elderly in China: Evidence from Chinese Longitudinal Healthy Longevity Survey

Abstract: As health challenging rural elderly in an aging population, more attention is being paid on impact of family intergenerational support on the health of the elderly. This paper investigates the effects of children’s intergenerational economic support and non-economic support on physical, mental, and functional health of rural elderly in China in the mean while. This paper applies the 2014 Chinese Longitudinal Healthy Longevity Survey (CLHLS), in particular, applying exploratory factor analysis to ascertain late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Empirical research regarding intergenerational support has had mixed results. Some studies suggest that intergenerational support is strongly associated with improved health, especially mental health, in the elderly ( Cong & Silverstein, 2008 ; Barnay & Juin, 2016 ; Shu et al, 2021 ). As a kind of informal care, intergenerational support, especially emotional support, can positively impact health by reducing the stresses of old age.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research regarding intergenerational support has had mixed results. Some studies suggest that intergenerational support is strongly associated with improved health, especially mental health, in the elderly ( Cong & Silverstein, 2008 ; Barnay & Juin, 2016 ; Shu et al, 2021 ). As a kind of informal care, intergenerational support, especially emotional support, can positively impact health by reducing the stresses of old age.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, we contribute to the literature by exploring both physical and psychological health outcomes in evaluating the effects of intergenerational care. Although existing studies have focused on either physical or mental health status among older parents ( Barnay & Juin, 2016 ; Shu et al, 2021 ; Wang & Li, 2012 ; Yang & Wen, 2021 ), health is multidimensional; using a single index of health may result in measurement errors ( Giles & Mu, 2007 ). Therefore, we used several measures of health, including self-reported health (SRH), activities of daily living (ADL), instrumental activities of daily living (IADL), mental health (CESD), and cognition to ensure robust results.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies still regard financial support from one’s children as well as their company and ability to provide care as necessary ways to improve the mental health of the elderly in rural China [ 10 ], which is not achievable, and the decline of support from one’s children is a mainstream trend. Therefore, some scholars have begun to seek other ways to improve the mental health of the elderly in rural China.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, support from family members, especially adult children, has a greater impact on health-promoting behaviors and healthy aging outcomes than other support from friends or neighbors [5][6][7]. Received intergeneration support, defined as a type of familial social support received by the elderly from their adult children [8,9], has been identified as having three types in the existing literature: financial, instrumental, and emotional support [10]. Until now, a wide variety of theoretical perspectives and studies have suggested that receiving intergenerational support influences elders' well-being-related outcomes [9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%